Mapping infectious disease hospital surge threats to lessons learnt in Singapore: a systems analysis and development of a framework to inform how to DECIDE on planning and response strategies - Shweta R. Singh; Richard Coker; Hubertus J-M Vrijhoef; Yee Sin Leo; Angela Chow; Poh Lian Lim; Qinghui Tan; Mark I-Cheng Chen; Zoe Jane-Lara Hildon (BMC, 2017)
Abstract Background Hospital usage and service demand during an Infectious Disease (ID) outbreak can tax the health system in different ways. Herein we conceptualize hospital surge elements, and lessons learnt from such events, to help build appropriately matched responses to future ID surge threats. Methods We used the Interpretive Descriptive qualitative approach. Interviews (n = 35) were conducted with governance and public health specialists; hospital based staff; and General Practitioners. Key policy literature in tandem with the interview data were used to iteratively generate a Hospital ID Surge framework. We anchored our narrative account within this framework, which is used to structure our analysis. Results A spectrum of surge threats from combinations of capacity (for crowding) and capability (for treatment complexity) demands were identified. Starting with the Pyramid scenario, or an influx of high screening rates flooding Emergency Departments, alongside fewer and manageable admissions; the Reverse-Pyramid occurs when few cases are screened and admitted but those that are, are complex; during a 'Black' scenario, the system is overburdened by both crowding and complexity. The Singapore hospital system is highly adapted to crowding, functioning remarkably well at constant near-full capacity in Peacetime and resilient to Endemic surges. We catalogue 26 strategies from lessons learnt relating to staffing, space, supplies and systems, crystalizing institutional memory. The DECIDE model advocates linking these strategies to types of surge threats and offers a step-by-step guide for coordinating outbreak planning and response. Conclusions Lack of a shared definition and decision making of surge threats had rendered the procedures somewhat duplicative. This burden was paradoxically exacerbated by a health system that highly prizes planning and forward thinking, but worked largely in silo until an ID crisis hit. Many such lessons can be put into play to further strengthen our current hospital governance and adapted to more diverse settings.